2014
DOI: 10.1128/aem.00251-14
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Prevalence of Lyme Disease Spirochetes in a Heterothermic Mammal, the Edible Dormouse (Glis glis)

Abstract: cIn Europe, dormice serve as competent reservoir hosts for particular genospecies of the tick-borne agent of Lyme disease (LD) and seem to support them more efficiently than do mice or voles. The longevity of edible dormice (Glis glis) and their attractiveness for ticks may result in a predominance of LD spirochetes in ticks questing in dormouse habitats. To investigate the role of edible dormice in the transmission cycle of LD spirochetes, we sampled skin tissue from the ear pinnae of dormice inhabiting five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Considering that nymphal I. ricinus ticks feed for 4 to 5 days (Matuschka et al 1991) and that, on average, every eighth nymph harbors B. afzelii in this region Matuschka 2006, 2011), the 4 % edible dormice parasitized by a nymph at any one time in June may receive an spirochetal inoculation within the span of 4 to 5 weeks (4 × 8 = 32 days). Indeed, we detected 3.6 % spirochetal prevalence in edible dormice a month later, during July (Fietz et al 2014b). That the increase in prevalence is delayed by about a month in respect to the increase in nymphal infestation rates supports also the interpretation of our previous finding that the population of edible dormice is only incrementally infected after a complete loss of spirochetal infection during hibernation.…”
Section: Seasonal Tick Infestation Rates On Edible Dormice Results In mentioning
confidence: 87%
See 4 more Smart Citations
“…Considering that nymphal I. ricinus ticks feed for 4 to 5 days (Matuschka et al 1991) and that, on average, every eighth nymph harbors B. afzelii in this region Matuschka 2006, 2011), the 4 % edible dormice parasitized by a nymph at any one time in June may receive an spirochetal inoculation within the span of 4 to 5 weeks (4 × 8 = 32 days). Indeed, we detected 3.6 % spirochetal prevalence in edible dormice a month later, during July (Fietz et al 2014b). That the increase in prevalence is delayed by about a month in respect to the increase in nymphal infestation rates supports also the interpretation of our previous finding that the population of edible dormice is only incrementally infected after a complete loss of spirochetal infection during hibernation.…”
Section: Seasonal Tick Infestation Rates On Edible Dormice Results In mentioning
confidence: 87%
“…In a previous study, we observed that none of the 103 edible dormice captured during May and June contained spirochetal DNA and only very few did so in July, although prevalence of infection in these populations reached 40 % in September (Fietz et al 2014b). Considering that LD spirochetes generally disseminate in their rodent host in the course of about 2 weeks (Richter et al 2002, the observed delay in prevalence may derive from either of three reasons: (a) edible dormice are not susceptible to tick-borne spirochetes at their emergence from hibernation and become more susceptible throughout the season, (b) spirochetal dissemination in edible dormice is somehow delayed compared with other rodents, or (c) the likelihood of edible dormice to encounter infected nymphal ticks increases during the course of the season.…”
Section: Seasonal Tick Infestation Rates On Edible Dormice Results In mentioning
confidence: 96%
See 3 more Smart Citations